2018
DOI: 10.24295/cpsstpea.2018.00003
|View full text |Cite
|
Sign up to set email alerts
|

Power System Support Functions Provided by Smart Inverters—A Review

Abstract: Renewable energy is seen as a viable alternative to traditional energy sources, and distributed generation (DG) based on renewable energy sources has experienced rapid growth worldwide. High penetration of renewable energy based DG systems makes the grid more vulnerable, and stricter standards have been issued for grid interconnection of DG systems. DG systems are expected to be controllable with high flexibility and reliability. Provision of grid support functions and ancillary services, such as reactive powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 57 publications
0
21
0
2
Order By: Relevance
“…Droop control may also be modified in order to allow output power flow regulation [126]. Harmonic attenuation functionalities are realized by damping the LCL-filter reactive behavior [127]- [130], by rejecting the grid-side harmonics [16], [111], [115], [117], [131]- [133], and by compensating the pollution possibly caused by local distorting loads [134].…”
Section: A Functionalities Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Droop control may also be modified in order to allow output power flow regulation [126]. Harmonic attenuation functionalities are realized by damping the LCL-filter reactive behavior [127]- [130], by rejecting the grid-side harmonics [16], [111], [115], [117], [131]- [133], and by compensating the pollution possibly caused by local distorting loads [134].…”
Section: A Functionalities Overviewmentioning
confidence: 99%
“…As far as abnormal conditions are concerned, perturbations like frequency variations [29], [115], voltage sags [135]- [138], and impedance variations [139]- [141] are commonly encountered, especially in weak grids. To minimize the impact of grid voltage sags on the power system, low-voltage ride through capabilities are often requested [137], [138].…”
Section: A Functionalities Overviewmentioning
confidence: 99%
“…The study in [9] proposed the voltage droop based autonomous reactive power control, it provides reactive power support to the grid based on change in grid voltage. X. Zhao et al reviewed the various functions used in the modern smart inverter unit and discussed the reactive power control strategies for the reliable operation of high DER penetrated power system [10]. Even though, various studies have been done regarding autonomous reactive power control in DER units, still several researches are required including: (i) response time for DER-reactive power support to the grid, since it is essential in practical applications in view of stability of the grid and protection devices employed in the system, (ii) maximizing the reactive power support to the grid considering safety voltage region of the distribution system.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the primary responsibility of the distribution system operator (DSO) is to bring the bus voltages above 0.88 pu to avoid the RES to cease operation 1 . In order to mitigate the voltage fluctuation problem due to massive penetration of DER in the network, 2,3 new‐generation smart inverters (SI) are incorporated by DERs to fulfill the ancillary service requirement, at reduced cost without any additional resources 4‐6 . In recent years, it is also observed that demand response (DR) programs are not only acting as a tool to allow customers to participate in the electricity market to improve the economic efficiency and reliability of distribution network 7‐9 but also improve the network voltage.…”
Section: Introductionmentioning
confidence: 99%